Tinjauan Pustaka Epilepsi: Prevalensi, Faktor Risiko, dan Komplikasi - Ni Wayan Puspa Wijaya Suryantarini (Faculty of Medicine, Universitas Mataram, 2025)
Epilepsy is one of the neurological diseases with increasing prevalence worldwide. Due to various factors, distribution of epilepsy is often observed to be higher in men, in children and the elderly, and in low-middle income countries. As a disease with heterogeneous etiology, the incidence of epilepsy is influenced by several risk factors that collaborate in the pathophysiological pathway of the disease. Head trauma, birth defects, central nervous system infections, and neurodegenerative diseases are associated with the incidence of epilepsy. With many obstacles to epilepsy management, the disease remains one of the causes of high mortality related to neurological diseases, especially in uncontrolled epilepsy conditions in patients who do not receive adequate treatment. This literature review aims to summarize the distribution of epilepsy cases from various countries in the world, including the associated risk factors reported in the period 2010-2024 using manual searching on PubMed and Google Scholar. Furthermore, the author discusses complications and prognostic factors in patients to emphasize the importance of comprehensive treatment to achieve remission and prevent relapse in patients.